Routledge encyclopedia of translation studies - Baker, Mona; Saldanha, Gabriela (Routledge, 2011)
Presents a comprehensive overview of the academic discipline of translation studies. This book covers the history of translation in major linguistic/cultural communities, and a range of fresh entries, including the Irish, Korean and South African traditions. It is suitable for students and teachers of translation, interpreting and literary theory